DESKRIPSI ANALISIS KEBUTUHAN PEMBELAJARAN FISIKA KELAS X DI SMA NEGERI 4 BANDAR LAMPUNG - Yuliana, Yuliana; Ertikantro, Chandra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This preliminary research studies about the learning needs of teachers and students in SMAN 4 Bandar Lampung.This preliminary research study consisted of field studies and literature.The purpose of this study is; (1) Know the teacher will need approprite learning media and can help students understand the concepts of Physics, (2) Determine the needs of students learning media will help students to learn the inquiry model,(3) to analyze the implementation of learning physics in SMAN 4 Bandar Lampung. This study used a descriptive method. This preliminary study was conducted in SMAN 4 Bandar Lampung dated 1 April 2015. With cluster sampling technique sampling,research subject X6 graders were 40 students and 3 teachers of Physics. Data obtained using a questionnaire and analyzed qualitatively through stages; Coding,data tabulation,analysis of qualitative data and make the appropriate interpretation of the results of analysis of problems and questions arise research and make conclusions. The findings of this preliminary study are; 1) Teachers and students of SMAN 4 Bandar Lampung already know the model of inquiry in learning, but its implementation is still using the model of lectures, discussions and assignments. 2) Teachers and students of SMAN 4 Bandar Lampung need instructional materials in the form of worksheets inquiry model with process skills approach that can help students understand the concepts of Physics. The conclusion of this study is to be developed LKS inquiry model in physics learning process skills approach. Keywords : inquiry model,prosess skills approach,and student worksheets.